Burial Mound Ladies - Gender, Age and Status in Mound Building Prehistoric Societies - Potrebica, Hrvoje; Arnold, Bettina (2010)
The lecture covers basic concepts of gender, age and status related to female burials and develop specific models related to those concepts within framework of mound building prehistoric societies.
Projekt MZOS
ENG